Spot‐on SERS Detection of Biomolecules with Laser‐Patterned Dot Arrays of Assembled Silver Nanowires. Issue 8 (19th February 2019) - Banchelli, Martina; Amicucci, Chiara; Ruggiero, Emmanuel; D'Andrea, Cristiano; Cottat, Maximilien; Ciofini, Daniele; Osticioli, Iacopo; Ghini, Giacomo; Siano, Salvatore; Pini, Roberto; de Angelis, Marella; Matteini, Paolo
Abstract: Unique characteristics of SERS including the possibility to reveal the compositional and structural content of trace amounts of biological samples without any pre‐treatment, depict this technique as a promising label‐free alternative to standard analytical methods. Despite significant advancements, current SERS substrates for biomolecule detection suffer from a number of issues still impeding their routine usage and commercial exploitation, including complex and expensive fabrication procedures and scarce standardization perspectives. Herein a combined bottom up/top down scheme based on flow‐through method plus laser patterning is proposed to prepare dot arrays of silver nanowires on a hydrophobic substrate for catching the analyte content from a minute amount of liquid sample and its rapid SERS inspection. As a consequence, a simple spot‐on analysis specifically adapted for reliable identification and characterization of molecules of biomedical interest is made possible. Our attempt may represent a concrete chance for progressing SERS toward widespread commercially viable sensing applications including diagnostics at the point‐of‐need settings and on‐site analyses. Abstract : In the spotlight : By implementing a mixed bottom‐up/top‐down approach, dot arrays of AgNWs clustered on hydrophobic supports are obtained and proven as efficient sensing surface‐enhanced Raman scattering (SERS) substrates for catching the analyte content from a minute amount of liquid sample and performing rapid SERS inspection.